Digital Creative Portfolios as New Spaces for Professional Interaction - Melendez Valoria, Verónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Since the advent of digital platforms that allowed creatives to publicly showcase their portfolios, some of these platforms have evolved beyond their original models. They have transitioned from mere exhibitions to more commercialized and interactive spaces. In these environments, any creative individual can not only display their work but also promote their brand and establish diverse connections, much like any other social network. The article aims to identify key elements and causes of this transformation. Additionally, it seeks to explain the position these platforms hold in relation to other domains. Lastly, it intends to extract implications and unresolved questions for reflection, considering their rapid evolution